Empagliflozin protects heart from inflammation and energy depletion via AMPK activation. (August 2020) - Koyani, Chintan N.; Plastira, Ioanna; Sourij, Harald; Hallström, Seth; Schmidt, Albrecht; Rainer, Peter P.; Bugger, Heiko; Frank, Saša; Malle, Ernst; von Lewinski, Dirk
Graphical abstract: Abstract: Aims: Sodium-glucose co-transporter 2 (SGLT2) were originally developed as kidney-targeting anti-diabetic drugs. However, due to their beneficial cardiac off-target effects (as SGLT2 is not expressed in the heart), these antagonists currently receive intense clinical interest in the context of heart failure (HF) in patients with or without diabetes mellitus (DM). Since the mechanisms by which these beneficial effects are mediated are still unclear yet, inflammation that is present in DM and HF has been proposed as a potential pharmacological intervention strategy. Therefore, we tested the hypothesis that the SGLT2 inhibitor, empagliflozin, displays anti-inflammatory potential along with its glucose-lowering property. Methods and Results: Lipopolysaccharide (LPS) was used to induce inflammation in vitro and in vivo . In cardiomyocytes and macrophages empagliflozin attenuated LPS-induced TNFα and iNOS expression. Analysis of intracellular signalling pathways suggested that empagliflozin activates AMP kinase (AMPK) in both cell types with or without LPS-treatment. Moreover, the SGLT2 inhibitor increased the expression of anti-inflammatory M2 marker proteins in LPS-treated macrophages. Additionally, empagliflozin-mediated AMPK activation prevented LPS-induced ATP/ADP depletion. In vivo administration of LPS in mice impaired cardiac contractility and aortic endothelial relaxation in response to acetylcholine, whereby co-administration of empagliflozin preserved cardiovascular function. These findings were accompanied by improved cardiac AMPK phosphorylation and ATP/ADP, reduced cardiac iNOS, plasma TNFα and creatine kinase MB levels. Conclusion: Our data identify a novel cardio protective mechanism of SGLT2 inhibitor, empagliflozin, suggesting that AMPK activation-mediated energy repletion and reduced inflammation contribute to the observed cardiovascular benefits of the drug in HF.